Epigenetic mechanisms in COPD: implications for pathogenesis and drug discovery. (June 2014) - Schamberger, Andrea C; Mise, Nikica; Meiners, Silke; Eickelberg, Oliver
Abstract : Introduction: Chronic obstructive pulmonary disease (COPD) is the fourth leading cause of death worldwide. The growing burden of COPD is due to continuous tobacco use, which is the most important risk factor of the disease, indoor fumes, occupational exposures and also aging of the world's population. Epigenetic mechanisms significantly contribute to COPD pathophysiology. Areas covered: This review focuses on disease-relevant changes in DNA modification, histone modification and non-coding RNA expression in COPD, and provides insight into novel therapeutic approaches modulating epigenetic mechanisms. Recent findings revealed, among others, globally changed DNA methylation patterns, decreased levels of histone deacetylases and reduced microRNAs levels in COPD. The authors also discuss a potential role of the chromatin silencing Polycomb group of proteins in COPD. Expert opinion: COPD is a highly complex disease and therapy development is complicated by the fact that many smokers develop both COPD and lung cancer. Of interest, combination therapies involving DNA methyltransferase inhibitors and anti-inflammatory drugs provide a promising approach, as they might be therapeutic for both COPD and cancer. Although the field of epigenetic research has virtually exploded over the last 10 years, particular efforts are required to enhance our knowledge of the COPD epigenome in order to successfully establish epigenetic-based therapies for this widespread disease.